Wolfsbane - Briggs, Patricia (New York : Ace Books, 2010)
Shapeshifting mercenary Aralorn leads a dangerous existence. Now she must return home, for her noble father, the Lyon of Lambshold, has passed away. But when Aralorn and her companion Wolf arrive, they find he's not dead but ensorcelled by the ae'Magi, who are using him as a conduit to destroy Aralorn and Wolf. She must overcome this mysterious mist or fall to the blackest of magic.
Sequel to: Masques.
Keywords: Shapeshifting -- Fiction; Mercenary troops -- Fiction; Magic -- Fiction; Fantasy fiction